A Consultative and Training workshop on the integration of CBBP in ATVET Program: Curriculum amendment and CBBP village Establishment - Belay, Berhanu; Getachew, Tesfaye; Haile, Aynalem (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
A community-based breeding program, an alternative genetic improvement approach, is expanding through collaborative action among stakeholders. CBBP has a scaling and commercialization framework through cooperative action. The research centers, the livestock extension program, and the Universities are engaged in advancing CBBP based on the scaling framework. ATEVETs through the Ministry of Labor and Skills are new organizations to CBBP that have shown interest in being involved in running CBBP in the areas of curriculum interventions, community-based breeding village establishment, and capacity-building training. In line with this effort, ICARDA undertook a consultative workshop by involving MoLS officials leading the Agricultural stream. The workshop brought together a total of 29 participants, from six ATEVT college deans, vice deans and as well as experts from the federal MoLS and scientists from ICARDA. The primary aim was to explore the integration of CBBP into the ATVET program. In this consultative and training workshop, the principles, practices, procedures, and notable achievements of CBBP were presented. In addition, the experiences of establishing CBBP in the Universities and the corresponding dividends of CBBP in enhancing teaching and learning, Community engagement and research were presented to encourage ATVET colleges to initiate CBBP programs. The discussion with the MoLS and ATVET college deans and vice deans showed that there is huge interest and commitment to initiating the CBBP. It was also noted that the ATVET colleges require capacity building training and monitor the programs. In conclusion, an action plan was developed and agreed upon to run a sequence of CBBP activities, with defined responsibilities assigned to each organization in implementing CBBP.